THE EFFECTIVENESS OF NATIONAL ZAKAT DISTRIBUTION IN 2024 IN ALLEVIATING POVERTY IN INDONESIA - Romdoni, Ahmad; Nurpalah, Jenal (Sekolah Tinggi Agama Islam Al Hidayah Bogor, 2025)
The effective distribution of zakat plays a crucial role in alleviating poverty in Indonesia; however, its realization and impact still face various challenges. This study aims to analyze the effectiveness of national zakat distribution in 2024 in reducing poverty rates and identifying the factors influencing its success. Using a quantitative approach through descriptive statistical analysis and regression, this study evaluates the correlation between zakat distribution and poverty levels based on data from BAZNAS and BPS. The findings indicate that zakat distribution contributes positively to poverty reduction, particularly in urban areas with a more organized distribution system, while in remote areas, its effectiveness is still hindered by institutional factors, accessibility, and transparency. Therefore, optimizing zakat distribution through improved governance, technology utilization, and synergy between the government and zakat management institutions is crucial to enhancing its impact on poverty alleviation. The proposed policy recommendations include zakat digitalization, capacity building for zakat administrators, and an empowerment-based approach for mustahik to ensure a more effective and sustainable role of zakat in addressing poverty in Indonesia.